Mn-Doping level dependence on the magnetic response of MnxFe3−xO4 ferrite nanoparticles. Issue 30 (10th July 2019) - Lasheras, Xabier; Insausti, Maite; de la Fuente, Jesús Martínez; Gil de Muro, Izaskun; Castellanos-Rubio, Idoia; Marcano, Lourdes; Fernández-Gubieda, Maria Luisa; Serrano, Aida; Martín-Rodríguez, Rosa; Garaio, Eneko; García, Jose Angel; Lezama, Luis
Abstract : Manganese/iron ferrite nanoparticles with different Mn 2+/3+ doping grades have been prepared by a thermal decomposition optimized approach so as to ascertain the doping effect on the magnetic hyperthermia response. Abstract : Manganese/iron ferrite nanoparticles with different Mn 2+/3+ doping grades have been prepared by a thermal decomposition optimized approach so as to ascertain the doping effect on magnetic properties and, especially, on the magnetic hyperthermia response. The oxidation state and interstitial position of Mn in the spinel structure is found to be critical. The particle size effect has also been studied by growing one of the prepared samples (from 10 to 15 nm in diameter) by a seed mediated growth mechanism. After analyzing the main structural and chemical parameters such as the Mn/Fe rate, crystalline structure, particle diameter, shape and organic coating, some Mn doping induced changes have been observed, such as the insertion of Mn 2+ cations yielded more anisotropic shapes. Magnetic characterization, carried out by DC magnetometry ( M ( H ), M ( T )) and electron magnetic resonance (EMR) techniques, has shown interesting differences between samples with varying compositions. Lower Mn doping levels lead to larger saturation magnetization values, while an increase of the Mn content causes the decrease of the effective magnetic anisotropy constant at low T . The homogeneous magnetic response under applied magnetic fields, together with the great effect of nanoparticle size and shape in such a response, has been confirmed by the EMR analysis. Finally, a detailed magnetic hyperthermia analysis has demonstrated the large influence of NP size and shape on the magnetic hyperthermia response. The optimized Mn0.13 Fe2.87 O4 _G sample with a diameter of 15 nm and slightly truncated octahedral shape is presented as an interesting candidate for future magnetic hyperthermia mediated biomedical treatments.